Pengaruh Brand Image, Product Quality, dan Brand Trust Terhadap Repurchase Intention Melalui Customer Satisfaction Produk Mustika Ratu di Kota Bandung - Mutiah, Ceha; Leni Evangalista Marliani (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The purpose of this study is to analyze the influence of brand image, product quality, and brand trust on repurchase intention, mediated by customer satisfaction, for Mustika Ratu face masks in the city of Bandung. The population in this study comprises consumers of Mustika Ratu face masks in the city of Bandung who have previously used Mustika Ratu face masks. The research employed convenience sampling, resulting in a sample of 150 respondents. Findings the research findings indicate that the brand image variable has a positive and significant impact on repurchase intention, while product quality and brand trust do not affect repurchase intention. Additionally, customer satisfaction plays a mediating role in the influence of brand image, product quality, and brand trust on repurchase intention. Product quality and brand trust do not directly and immediately drive repurchase intention. Further research is needed for these variables.